2018
DOI: 10.21037/jtd.2018.08.32
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for parasitic lung infestations: roles in diagnosis and treatment

Abstract: Pulmonary parasitic infestations are a worldwide problem associated with significant morbidity and socioeconomic impact. They are known to have varied clinical presentations and radiological appearances. Prevention of parasite transmission and medical treatment of cases form the two pillars of control of these diseases. The role of surgery is limited to the diagnosis and definitive treatment of the minority of pulmonary parasitic afflictions, most notably hydatidosis. Despite surgery being established as the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 85 publications
(71 reference statements)
1
27
0
Order By: Relevance
“…Patients with intact cysts are usually asymptomatic; however, some do develop symptoms such as cough, dyspnoea, fever and chest pain. [4] A chest radiograph is the first radiological analysis that is performed for all patients with pulmonary hydatid disease and its diagnostic value for intact cysts is very high. [8] A contrast-enhanced CT scan of the chest and upper abdomen should be performed to confirm the diagnosis, identify liver and splenic cysts and help with the planning of the necessary surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients with intact cysts are usually asymptomatic; however, some do develop symptoms such as cough, dyspnoea, fever and chest pain. [4] A chest radiograph is the first radiological analysis that is performed for all patients with pulmonary hydatid disease and its diagnostic value for intact cysts is very high. [8] A contrast-enhanced CT scan of the chest and upper abdomen should be performed to confirm the diagnosis, identify liver and splenic cysts and help with the planning of the necessary surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Children have more elastic lung tissues, tend to have larger cysts and delayed presentation. [4] Furthermore, they may present with so-called giant cysts (≥10 cm in size). [4] In a study of 1 055 patients in Turkey, [11] most cysts were found in the lower lobes compared with upper lobes and in the right lung compared with the left lung.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations